Integrating digital health competencies in community-engaged medical education: A scoping review for developing teaching and learning strategies for digital health - Jaime Kristoffer Punzalan; Mary Germeyn Punzalan (Journal of Education and Health Promotion)
This study investigates the integration of digital health competencies within a community-engaged medical education (CEME) framework. This review explores and develops effective strategies for incorporating digital health competencies into medical curricula. By focusing on community engagement, the study seeks to align medical education with real-world health challenges, bridging the gap between theoretical knowledge and its practical application. The methodology involves a scoping review using databases such as PubMed/MEDLINE, Google Scholar, and Science Direct, focusing on the last 5 years of research on digital health competencies in medical education. A structured data charting process used an abstraction form to extract relevant information from eligible studies. Key findings from the study emphasize the necessity for a curriculum that enhances students’ understanding and practical application of digital health tools. Students require training that blends theoretical knowledge with practical applications, ensuring adaptability to the latest digital technologies and methodologies. Continuous professional development is necessary for faculty to remain adept at teaching these advanced concepts. Furthermore, curriculum management must ensure that digital health education is dynamic with continuous curriculum updates. The educational context should be supportive and dynamic, encouraging student-centered learning. Lastly, community engagement fosters culturally sensitive and inclusive educational practices. These collaborations enhance learning and ensure that digital health solutions are effectively implemented in community settings, particularly benefiting underserved populations. Integrating digital health competencies into CEME represents mitigating healthcare disparities and equipping future healthcare professionals with the necessary tools to deliver competent, culturally aware, and technologically proficient care.